METHOD FOR INVESTIGATION OF CAPACITY LOSSES FOR FRICTION IN CYLINDER-PISTON GROUP - V. V. Alferovich (Наука и техника)
The paper contains a method and a scheme of the device for investigation of energy losses in a cylinder-piston group of internal combustion engine. The method for a separate determination of capacity losses for friction in piston rings and a piston itself is described in the paper.